Barriers to the Innovative Activities of Lower Silesian Enterprises - Głuszczuk, Dariusz (Bariery działalności innowacyjnej dolnośląskich przedsiębiorstw, 2023)
The innovation of enterprises and regions constitutes one of the key foundations in building a competitive advantage. In this context, innovative activity, its determinants and barriers become of particular importance. This article focuses on the barriers to innovation, comparing the source literature with the solutions offered by official statistics in terms of the relevant terminology and the distribution of constraints to innovation. The empirical research aimed to identify the major barriers to the innovative activities of Lower Silesian enterprises, and capture possible differences in the perception of obstacles to innovation in the environment of industrial and service enterprises viewed from the perspective of 2019 and 2021. The analyses indicate that regional manufacturers and service providers face similar barriers to innovation (e.g. cost factors), but that these are much more frequently observed in the industrial sector. The research procedure employed the methods of source literature critical analysis and descriptive statistics.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 11-21
Keywords: barriers to innovation activities; Lower Silesian enterprises; Oslo Manual; bariery działalności innowacyjnej; dolnośląskie przedsiębiorstwa; podręcznik Oslo